An ICT-guided ratiometric naphthalene–benzothiazole-based probe for the detection of cyanide with real-time applications in human breast cancer cells. Issue 33 (9th August 2022) - Banerjee, Shilpita; Mandal, Moumi; Halder, Satyajit; Karak, Anirban; Banik, Dipanjan; Jana, Kuladip; Mahapatra, Ajit Kumar
Abstract : The probe MNBTZ reacts with cyanide by inhibiting ICT and resulting in a ratiometric fluorescence change from bright yellow to light purple. The hypsochromic shift in wavelength can be seen in the human breast cancer cell imaging study. Abstract : A methoxynaphthalene benzothiazole conjugate (MNBTZ ) armed with CC vinylic double bonds was synthesized and utilized for the selective detection of CN − ions. The probe showed yellow fluorescence due to ICT from the methoxynaphthalene moiety to benzothiazole, which instantly changed to light purple upon the nucleophilic addition of CN − to the vinylic double bond, inhibiting ICT due to the break-in conjugation. The effectiveness of the probe was proved by this brilliant ratiometric fluorescence change, which was achieved selectively as observed by experiments with competing anions. 1 H NMR titrations and DFT calculations support this mechanism. A low detection limit of 2.1(±0.0022) × 10 −8 M along with good fluorescence color change on solid TLC plates and human breast cancer cells makes it amenable to CN − sensing.